2017
DOI: 10.1186/s13028-017-0343-7
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of zoonotic trematodes in roach (Rutilus rutilus) in the Gulf of Finland

Abstract: The intention to increase roach (Rutilus rutilus) consumption is in focus for ecological and economic reasons in Finland. However, its safety as food has not been considered comprehensively. We collected and artificially digested 85 roach halves originating from the south-eastern coast of Finland, and found trematode metacercariae in 98.8% of the samples. Based on polymerase chain reaction (PCR) and sequencing of amplicons generated from the ITS2 gene region, zoonotic parasites of the family Opistorchiidae wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…metacercariae were different in size and shape from those of Holostephanus metorchis (164× 140 µm in average size) from a fish, Pseudorasbora parva, found in the Republic of Korea, and the cyst wall was thinner than that of H. metorchis [28]. Previous studies reported that the roach (Rutilus rutilus) found in the Gulf of Finland is considered a second intermediate host of H. dubinini [29].…”
Section: Discussionmentioning
confidence: 85%
“…metacercariae were different in size and shape from those of Holostephanus metorchis (164× 140 µm in average size) from a fish, Pseudorasbora parva, found in the Republic of Korea, and the cyst wall was thinner than that of H. metorchis [28]. Previous studies reported that the roach (Rutilus rutilus) found in the Gulf of Finland is considered a second intermediate host of H. dubinini [29].…”
Section: Discussionmentioning
confidence: 85%
“…Roach exhibited the highest species richness in both Lyngby Sø (five species) and Bromme Lillesø (six species) consistent with previous studies on freshwater fish in Poland (Dzika et al, 2008). No zoonotic parasites were discovered in roach in our study, but zoonotic opisthorchid metacercariae (Pseudamphistomum truncatum) were previously reported from roach in the Danish lake Furesø (Skov et al, 2008) and in the Gulf of Finland (Eriksson-Kallio et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The taxon is considered monophyletic representing an ancient digenean lineage ( Achatz et al, 2019 ). The presence of cyathocotylid metacercarie in various freshwater fishes was documented in Czechia ( Kvach et al, 2016 ), Finland ( Näreaho et al, 2017 ), France ( Gettová et al, 2016 ), Slovakia ( Ondračková et al, 2009 ) and Russia ( Kvach et al, 2015 ). Human infections have not been documented but mammals (dogs) have been suggested as potential hosts of adult cyathocotylids ( Chandler, 1950 ; El-Assal et al, 1986 ).…”
Section: Introductionmentioning
confidence: 99%